1968
DOI: 10.1097/00006842-196801000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Obese Patients to Weight Reduction: A Clinical Evaluation of Behavior

Abstract: Studies of the behavioral responses of obese patients during weight reduction present conflicting observations. This is due, in part, to methodologic problems. A possible solution is offered by a multidisciplinary investigation of obese patients before, during, and after weight reduction. This report gives details of one aspect of such an approach; namely, a clinical evaluation of psychopathologic reactions and psychodynamic processes of obese patients during weight loss.Four obese patients were fed a 600-cal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

1973
1973
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 23 publications
2
17
0
4
Order By: Relevance
“…1 Robinson and Winnik (1973) report that, during severe dietary restriction, obese patients with no history of psychiatric disorders manifested a variety of impulsive behaviors, including exhibitionism and suicidality; Kollar and Atkinson (1966) and likewise report suicidality. Uncontrollable binge eating is common during therapeutic starvation Glucksman, Hirsch, McCully, Barron, & Knittle, 1968;Kollar & Atkinson, 1966;Swanson & Dinello, 1970). While this may not be surprising given the subjects' initial problems with food, less expected are the marked changes in emotion: Many investigators report dramatic increases in anger and aggression, in some cases constituting a stunning 1 The therapeutic aspect of these procedures is highly questionable.…”
Section: Evidence From Obese Subjectsmentioning
confidence: 99%
“…1 Robinson and Winnik (1973) report that, during severe dietary restriction, obese patients with no history of psychiatric disorders manifested a variety of impulsive behaviors, including exhibitionism and suicidality; Kollar and Atkinson (1966) and likewise report suicidality. Uncontrollable binge eating is common during therapeutic starvation Glucksman, Hirsch, McCully, Barron, & Knittle, 1968;Kollar & Atkinson, 1966;Swanson & Dinello, 1970). While this may not be surprising given the subjects' initial problems with food, less expected are the marked changes in emotion: Many investigators report dramatic increases in anger and aggression, in some cases constituting a stunning 1 The therapeutic aspect of these procedures is highly questionable.…”
Section: Evidence From Obese Subjectsmentioning
confidence: 99%
“…The existence of such a weight threshold was also proposed by Glucksman and Hirsch. 32 Solow and Silverfarb35 and Kalucy and Crisp36 found that massively obese people, losing weight after ileojejunal bypass, showed little tendency to develop depression but there were often major changes in their life styles which affected people living with them. They concluded that food deprivation, to which these obese patients losing weight were not exposed, might be an important factor generating depression in those losing weight through restriction of diet.…”
Section: Measurementsmentioning
confidence: 99%
“…The discrepancy between women's perceived and ideal body size has been used to detect body dissatisfaction and bulimic tendencies [Cash and Deagle 1997], because people with eating disorders do not veridically perceive their own body size [Glucksman and Jules 1968;Cash and Deagle 1997;Smeets et al 1997] (see Farrell et al [2005] for an overview). More specifically, patients who are anorexic tend to overestimate the size of their body [McCabe et al 2001], whereas patients who are obese underestimate both their own and the body size of others [Glucksman and Jules 1968;Doolen et al 2009].…”
Section: Introductionmentioning
confidence: 99%